2012
DOI: 10.1007/s00214-012-1149-3
|View full text |Cite
|
Sign up to set email alerts
|

Hunting dimers

Abstract: HBCBH and HAlCAlH are related electrondeficient molecules, predicted as local minima on their respective potential energy surfaces. Different views of their electronic structure-as allenes, carbenes, or carbones-prompted two research groups to a friendly competition exploring the predilection of these small molecules to dimerize. Many such dimers emerged from the calculations, some with large enthalpies favoring dimerization. Most interesting among these is an octahedral didehydrocarborane (or alane). The mena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The process is shown schematically in Figure 6b, which depicts an initial carbone HB→C←BH reference structure, whose carbon σ lone pair is subsequently donated into the empty in‐plane p AOs of boron. An alternative view is provided by a cyclic C(BH) 2 reference structure with an “inverted” carbene54 configuration that donates charge into the vacant carbon σ lone‐pair orbital (Figure 6c) 55. Both perspectives come to the same conclusion: the HOMO−1 in bent C(BH) 2 enhances carbon–boron bonding, it yields partial boron–boron bonding, and it has some (reduced) σ lone‐pair character.…”
Section: Resultsmentioning
confidence: 99%
“…The process is shown schematically in Figure 6b, which depicts an initial carbone HB→C←BH reference structure, whose carbon σ lone pair is subsequently donated into the empty in‐plane p AOs of boron. An alternative view is provided by a cyclic C(BH) 2 reference structure with an “inverted” carbene54 configuration that donates charge into the vacant carbon σ lone‐pair orbital (Figure 6c) 55. Both perspectives come to the same conclusion: the HOMO−1 in bent C(BH) 2 enhances carbon–boron bonding, it yields partial boron–boron bonding, and it has some (reduced) σ lone‐pair character.…”
Section: Resultsmentioning
confidence: 99%
“…To our surprise, in a recent computational study, 04 was predicted to have a perfect D 4h -cage at the BP86/def2-TZVPP level. 7 So, we performed extra optimizations for isomer 04 using eight exchangecorrelation functionals, e.g., BP86, X3LYP, M062X, WB97XD, B3PW91, PBEPBE, PBEPW91 and HSEH1PBE with aug-cc-pVTZ basis set. Table 2 lists the energy difference at the CCSD(T)/augcc-pVTZ + ZPEC level based on various DFT geometries between the global minimum and the hypercloso cage.…”
Section: Resultsmentioning
confidence: 99%
“…Here, through extensive isomeric searching, we report an abnormal example C 2 B 4 H 4 , whose global minimum is a ribbon-like isomer at the CCSD(T) aug-cc-pVTZ//B3LYP/aug-cc-pVTZ level, instead of the octahedrallike hypercloso species that was revealed in a recent theoretical study. 7 The detailed calculation strategy, results and discussions can be found in the following sections.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the group of Frenking and Hoffmann reported the theoretical studies on a C 2 B 4 H 4 cluster, and concluded that the favored structure is the hypercloso octahedron I involving two capped carbon atoms (Fig. 1a) 21 . By contrast, Ding and coworkers proposed that the global minima of the C 2 B 4 H 4 cluster is a ribbon-like isomer II, which lies 16.0 kcal mol −1 lower in energy than I 22 .…”
mentioning
confidence: 99%